PENGARUH TERAPI BACAAN AL-MATSURAT TERHADAP NYERI DISMENOREA PADA MAHASISWI KEPERAWATAN - Rahmi Musaddas (IKesT Muhammadiyah Palembang, 2023)
Introduction: Dysmenorrhea is painful uterine pain that occurs before and during menstruation. Al-Ma'surat is a collection of dhikr readings selected by Hasan al-Banna from a number of verses and hadiths of the Prophet Muhammad. The intervention used for al-Matsurat reading therapy for dysmenorrhea pain used the lecturing method. The purpose of the study: to determine the effect of almatsurat reading therapy on the level of dysmenorrhea pain in Nursing Students Research Methods: This study used a quasi-experimental design with the One Groups Pretest-Posttest Design approach with a sample were 32 respondents. The sampling technique used Total Sampling. The research instrument used a questionnaire sheet. Data analysis used univariate and bivariate analysis with paired sample t test statistics. Results: The average pain of dysmenorrhea before being given almatsurat reading therapy was 5.97. The average score for dysmenorrhea after being given almat letter reading therapy was 3.75. Conclusion: There is an effect of before and after health education on knowledge (p value = 0.000).